Implementation of Digital Learning Media to Improve Student Learning Outcomes on Dry Skin Care Material - Nurhayati, Ifa; Olivia, Alila; Mawalia, Annisa; Amalia, Ashiffa Fatikha; Mithalinda, Ayesha Nabila; Definta, Aufa Manda; Chairunnisa, Dhea Aprilia; Fitriani, Farida; Queenasyifa, Queenasyifa; Putri, Indah Selfiana; Legawa, Kayla Putri; Sarah, Kirana Alanis; Aulia, Khansa; Septriana, Nadilla; Listiana, Ridainisa Dwi; Nefi, Rosa; Hasanah, Selvi Hasnita (Universitas Negeri Semarang, 2025)
The rapid advancement of digital technology has significantly transformed the education sector, including the field of cosmetology and skin care. This study aims to review the implementation of digital learning media in improving students’ learning outcomes on dry skin care materials. The review was conducted by analyzing 15 scientific articles, consisting of 10 international and 5 national journals published between 2016 and 2025. The findings reveal that digital learning media such as interactive videos, e-learning modules, mobile learning applications, and virtual simulations, consistently enhance students’ conceptual understanding, practical skills, and learning motivation. Digital based learning fosters a more flexible, interactive, and student centered learning environment, leading to better knowledge retention and clinical performance. However, its effectiveness highly depends on the quality of instructional design, technological infrastructure, and instructors’ ability to integrate digital tools into teaching. This review recommends adopting a blended learning model that combines digital media with hands on laboratory practice and developing contextually relevant learning content. Therefore, digital learning media can serve as an innovative strategy to improve students’ learning outcomes, particularly in mastering dry skin care competencies.